Development of Flipbook Learning Media to Improve Learning Outcomes IPAS - Fani Yustina Putri Pigai; Sigit Yulianto (Jurnal Penelitian Pendidikan IPA, 2024)
Utilizing digital learning media is something that teachers need to do. This is because learning media is an important learning role. The lack of use of innovative and creative learning media can result in student learning outcomes not being achieved optimally, especially in class IV science subjects on plant body parts and their functions. This research was conducted with the aim of creating and developing Flipbook learning media which can be used as a means of delivering material to students. This research uses Research and Development research with the ADDIE research model. Furthermore, the researcher's data analysis technique used the normality test, n-gain test and t-test which were processed with the SPSS 23 application. The expert validator lecturer's assessment obtained a percentage result of 93.75% in the very feasible category. The results of the normality test in this study obtained a pretest result of 0.52 and a posttest value of sig. = 0.36 which indicates that the data is normally distributed. The next analysis is the n-gain test which produces the result that the n-gain score is 0.46 which shows an increase in the value in the medium category and the last one is the t-test which produces t-test calculations for pretest and posttest questions showing results that are sig. (2-tailed), namely 0.000, indicates a significant difference between the pretest and posttest. Through research and assessment of the test results, there is an increase in student scores as seen from the pretest and posttest learning results. Thus, it can be concluded that the Flipbook learning media is very suitable and effective for use in teaching and learning activities, especially in class IV science subjects regarding plant body parts and their functions.